Difficulties in Reliability Evaluation of Microprocessor Protections - Uspensky, M. (Techniques and Innovation in Engineering Research Vol. 4, 2022)
Among the main characteristics of the relay protection functioning are reliability indicators. With the transition to the execution of such protections on a microprocessor-based basis, in addition to hardware reliability, it became necessary to characterize its operation by software reliability. Importance of the tasks in the operation process refers it the programs used in safety-critical software and operating in the real mode. This in turn, tightens the requirements for their reliability evaluation. General requirements for programs of critical applications are considered. Features characteristic of microprocessor protection programs are proposed. An example of such an assessment is given.